2017
DOI: 10.1073/pnas.1620312114
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin potentiates transcription

Abstract: Chromatin isolated from the chromosomal locus of the PHO5 gene of yeast in a transcriptionally repressed state was transcribed with 12 pure proteins (80 polypeptides): RNA polymerase II, six general transcription factors, TFIIS, the Pho4 gene activator protein, and the SAGA, SWI/SNF, and Mediator complexes. Contrary to expectation, a nucleosome occluding the TATA box and transcription start sites did not impede transcription but rather, enhanced it: the level of chromatin transcription was at least sevenfold g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…As in vitro transcription from chromatin templates isolated from cells was significantly enhanced by histone acetylation (15), the induction of these genes is likely dependent on the subsequent acetylation of histones mediated by local regeneration of nuclear acetyl-CoA. As such, the nuclear presence of the ACSS2 enzyme enables the effects of a local acetate signal to be magnified and broadcast through epigenetic regulation of genes involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As in vitro transcription from chromatin templates isolated from cells was significantly enhanced by histone acetylation (15), the induction of these genes is likely dependent on the subsequent acetylation of histones mediated by local regeneration of nuclear acetyl-CoA. As such, the nuclear presence of the ACSS2 enzyme enables the effects of a local acetate signal to be magnified and broadcast through epigenetic regulation of genes involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on in vitro reconstitution of yeast and mammalian nucleosomes suggested that mammalian nucleosomes bind DNA more readily (80% chromatin assembly), and that yeast nucleosomes are comparatively unstable (~16% assembly) (Lee et al, 1982). Furthermore, it has long been known that in vitro transcription using human chromatin (or any higher eukaryote chromatin) inhibits transcription (Konesky and Laybourn, 2007; Lorch et al, 1987), but a recent paper using native yeast chromatin showed enhanced in vitro transcription compared to naked DNA (Nagai et al, 2017). Our study may provide a means to reconcile these opposing observations.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Purification SWI/SNF was purified from Saccharomyces cerivisiae using a modified TAP purification as described in Nagai et al 35,36 . A strain modified with a TAP tag on the C terminus of SNF2 was obtained from GE Dharmacon and grown at 30 °C in YPD.…”
Section: Methodsmentioning
confidence: 99%